Views on alternatives to imprisonment: a citizens jury approach - Corinne Walsh
Abstract Alarming over-representation of Aboriginal and Torres Strait Islander people in Australian prisons, combined with high recidivism rates and poor health and social outcomes among those released from prison, has led many to claim that incarceration is a social policy failure. An important obstacle to a reform agenda in the criminal justice area is public opinion. The public are often perceived to hold punitive attitudes towards offenders, a situation often exploited by politicians to perpetuate punitive penal policies at the expense of developing decarceration initiatives. However, alternatives to public opinion surveys/polls are needed to assess the public’s views, as survey/poll-based methods typically present shallow, unconsidered public opinion and thwart good policy development and reform. Citizens Juries offer an alternative method to assess the public’s views, views that are critically informed and thus better aid policy development. This project aimed to explore, through Citizens Juries, the views of a critically informed public in three states/territories towards how we, as a community, should address offenders in terms of incarceration and incarceration alternatives. The research focused on a range of incarceration alternatives including Justice Reinvestment. The study also aimed to examine the thoughts of senior policymakers on the outcomes of Citizens Juries. This research provides important information and evidence in the offender health area and contributes to the Justice Reinvestment debate among offender health, criminal justice, political and community stakeholders.&nbsp